Transforming Business Education Curriculum for the Digital Economy: Challenges and Strategic Opportunities - Imam Yuwono; Ahmad Maulidizen; Ahmad Reza Hariyadi; Muhammad Saleem Iqbal (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2026)
This study examines the transformation of business education curricula in response to the rapid expansion of the digital economy. The increasing integration of artificial intelligence, big data analytics, cloud computing, and digital platforms has significantly reshaped industrial demands and professional competencies. Using a qualitative research approach and content analysis, this study explores the challenges and strategic opportunities associated with curriculum transformation in higher education institutions. The findings reveal that universities face critical challenges related to technological infrastructure, faculty readiness, curriculum relevance, and industry alignment. However, digital transformation also provides opportunities for interdisciplinary learning, experiential education, global collaboration, and technology-driven innovation. The study emphasizes the importance of adaptive leadership, faculty development, industry partnerships, and student-centered pedagogies in supporting sustainable curriculum reform. Ultimately, transforming business education curricula is essential for preparing graduates with digital competencies, critical thinking abilities, and innovative skills necessary to compete effectively in the global digital economy.